High intake of sweet foods and low life satisfaction can act as risk factors for acute coronary syndrome through synergistic interaction - So, Jisun; Chung, Kyong-Mee; Seo, Jihyeon; Kim, Byungmi; Chun, Hyejin; Han, Sung Nim; Chung, Ick-Mo (Frontiers in Nutrition, 2023)
Purpose: Dietary and psychological status contributes to development of coronary artery disease. However, these lifestyle factors may vary depending on ethnic and environmental background, and secondary prevention programs dealing with these factors in specific population are not well established. We aimed to assess dietary and psychological characteristics in patients with acute coronary syndrome (ACS), and analyze their interaction as independent risk factors for ACS. Methods: Ninety-two patients with ACS (29 acute myocardial infarction, 63 unstable angina) and 69 controls were subject to dietary and psychological analyses. Dietary intake was assessed by a food frequency questionnaire. Psychological depression and perceived stress were assessed by Patient Health Questionnaire-9 and Perceived Stress Scale, respectively. Eight domains of life satisfaction (love relationship, leisure, standard of living, job, health, family life, sex life, and self) were assessed by the Domain Satisfaction Questionnaire (DSQ). Results: The ACS group had higher consumption of sweets and fish/seafood, as well as higher levels of depressive symptoms. Additionally, they had lower DSQ scores in total as well as in all 8 individual domains compared to the control group. In multivariate logistic regression analysis sweet intakes (OR 4.57, 95% CI: 1.94-11.40) and total DSQ scores (OR 0.34, 95% CI: 0.14-0.81) were identified as independent risk factors for ACS. Furthermore, these factors, which displayed a significant inverse correlation (rho = -0.23, p=0.01), were determined as having a synergistic contribution to the development of ACS. Conclusions: High sweet food intake and low life satisfaction can act as risk factors for ACS through a synergistic interaction, which emphasizes a demand for a more comprehensive approach in secondary prevention of ACS. In additions, these data highlight the role of positive psychological well-being factor in cardiovascular health.